Revision of Gossypariella Borchsenius with description of new species (Homoptera Coccoidea Eriococcidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The genus Gossypariella is revised with the description of two new species and redescription of two species, and designation of lectotype of the generic type.
Keywords: scale insects; Homoptera; Coccoidea; Eriococcidae; Gossypariella; new species; revision; key